Blended learning as an optimal strategy for teacher's professional development: systematic literature review - Huang, Yanfen; Syed-Abdullah, Sharifah Intan Sharina; Zulkifli, Nurul Nadwa; Ghazali, Norliza (UK Zhende Publishing Group, 2023)
The impact of blended learning (BL) is growing in teacher education, and more and more teacher professional development activities are using BL strategies. A systematic review of research on blended teacher-professional development (BTPD) can enable us to develop better teacher-professional development (TPD) programs. This systematic literature review takes 90 papers from 2015 to 2021 retrieved from four databases in April 2022 as the analysis objects. to analyze the status and trends of BL strategy used in TPD programs. The review covers the dimensions of the research background, research methods, and research findings. Findings show that the number of studies on BTPD increases year by year. The research mostly focused on BL for the professional development of K-12 and pre-service teachers, particularly their learning in information, communication, and technology (ICT). The research topics of the reviewed papers pay more attention to instructional design and learning effect analysis. Most studies believe that BL is an effective strategy for TPD. The review also found that BL strategies have some potential to promote education for sustainable development and educational equity. However, the limitation of BTPD strategies is that they require the cooperation of multiple organizational structures to work optimally.